A Review of Texture Related Corrosion of Thin Metallic Films - Seo, Jong H.; Lee, Dong Nyung (Innovations in Corrosion and Materials Science (Discontinued), 2014)
Most of electrochemical properties of thin materials are closely related with the microstructure of the thin films. In this paper, we review the preferred orientation dependency of metals in aqueous solutions. For example, aluminum foil etching in highly concentrated hydrochloric acid solution, etching of invar sheet for shadow masks, and texture related stress corrosion cracking of metals and alloys are discussed. All the phenomena were interpreted in terms of elastic properties of thin films and bulk materials.
Keywords: thin film